DIETARY IMPACT ON THE ANTICOAGULANT EFFICACY OF VITAMIN K ANTAGONISTS - Natalia Bukała; Dominika Kondyjowska; Dorota Maria Komuńska; Sylwia Tomasiczek; Weronika Tomasiczek; Zuzanna Sawiec; Ewa Antonowicz; Marta Rogozińska (International Journal of Innovative Technologies in Social Science, 2026)
Background: The vitamin K antagonists’ (VKA) mechanism of action is closely related to the metabolic pathways of vitamin K. Dietary vitamin K intake can directly translate into efficacy of VKA therapy.Aim: The aim of the study was to summarize information about the role of vitamin K in the coagulation process and its impact on Vitamin K Antagonists.Material and methods: A non-systematic litrerature review was conducted using databases such as Pubmed and Cochrane Database. Search terms included VKA pharmacokinetics, INR targets and dietary management strategies.Results: Irregular intake of vitamin K negatively affects the action of hydroxycoumarin derivatives by causing INR fluctuations and subtherapeutic anticoagulation.  Excessive doses of vitamin K reduce VKA activity and increase risk of side effects such as thromboembolic complications.Conclusions: Effective anticoagulation with VKAs requires personalized dosage, regular INR monitoring and conscious management of vitamin K intake.